Sistem Informasi Arus Kas Dengan Metode Cash Basis Pada TK Mekarsari Sidokumpul Patean Kendal - Munifah Munifah; Kasih Purwantini; Eli Septiani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Mekarsari Kindergarten is a private school that was founded in 2015 with C accreditation and has one classroom located in Cipluk Sidokumpul Hamlet, Patean Kendal District, Central Java. As for the information system for receipts and expenditures in educational institutions, which still uses a manual system, in the data input process until the report is still written in recording financial transactions, especially in cash receipts and expenditures, by recording cash receipts and disbursements on receipts, then the information is summarized and recorded in the cash ledger. This makes the cycle spend most of its time in presenting financial reports, data discrepancies and large levels of errors can occur due to the large number of transactions that have been carried out, and double or double recording occurs if recorded manually. In addition, the speed of data input to report information may be late if needed at any time. This research aims to design a cash flow information system using the cash basis method, which makes it easier to record cash receipts and disbursements at Kindergarten Mekarsari Sidokumpul Patean Kendal using a computerized system. Building an effective and efficient information system in presenting financial reports. And minimize errors and deficiencies in input because every money received is immediately recorded into the system.